The Shehata technique for undescended testes that cannot be brought into the scrotum in one operation—a case series and meta-analysis - Lin, Zhenying; Yu, Zhongjing; Li, Huanyuan; Wu ri ni, Letu; Zhang, Baoxin (Frontiers in Pediatrics, 2024)
Background: Fowler-Stephens orchiopexy is commonly used for testes that cannot be brought into the scrotum in one operation. However, this surgical technique may result in a higher rate of testicular atrophy postoperatively. Methods: We analyzed 20 cases of Shehata technique for testes that cannot be brought to the scrotum in one operation, from 2019 to 2023, and conducted a meta-analysis to explore the incidence of testicular atrophy between Shehata technique and Fowler-Stephens orchiopexy. Results: The average age of 20 patients was 3.78 (0.76-11.42) years. The blood supply to the testes was satisfactory, without any atrophy, and the testes could be brought to the scrotum in stage II surgery. Postoperative reexamination with ultrasound revealed that the testes were securely positioned within the scrotum, with a good blood supply and no atrophy compared to their condition before the operation. The volume of the testes postoperatively was significantly greater than that of the preoperative testes (p = 0.009). There were no statistically significant differences in the growth rate of the testes' volume between the surgically treated side and the contralateral side (p = 0.25). The meta-analysis showed that the Shehata technique had a lower incidence of testicular atrophy compared with Fowler-Stephens orchiopexy (p = 0.01). Conclusions: The Shehata technique preserves the main vessels of the testes with lower incidence of testicular atrophy, which may be a valid and safe alternative to the Fowler-Stephens technique.